The Dr. Lino Alarco and his time - Graña Aramburú, Alejandro (2008)
The Dr. Lino Alarco was a distinguished surgeon who was a pioneer in performing advanced, daring, and even unthinkable surgical procedures during the second half of the 19th century in Peru. Lino Alarco was ahead of his time, and he made precise descriptions of both benign and malignant tumors. On June 12th, 1878, Dr. Alarco performed the most daring procedure in his career. He excised a tumoral ovarian cyst in the patients home, and he became the very first surgeon in performing intraperitoneal surgery in Peru.